Optimization and Physical Characterization of Kojic Acid Nanoemulsion Formula As A Whitening Agent - Yovi Guanse; Rini Dwiastuti; Brigita Tuelvin Jenita Gandi; Lutfi Chabib (Sanata Dharma University, 2025)
Kojic acid (KA) as a topical formulation prevents hyperpigmentation through the inhibition of tyrosinase activity. However, KA has higher solubility in nonpolar solvents. Nanoparticle technology can be a novel innovation to enhance KA absorption into the skin. This study aims to improve the delivery of topically applied KA by enhancing absorption into the stratum corneum by optimizing the concentration of surfactant Tween 80 and co-surfactant Span 80. The nanoemulsion uses KA as an active ingredient and virgin coconut oil as the oil phase. The optimum area was analyzed using Design-Expert® 13 software, with a pure experimental design based on a 2x2 factorial design. The results indicate that all formulas are within the optimal region. Therefore, the determination of the optimal point can be grounded on the smallest composition within the optimal region with the objective of maximizing material efficiency, which is a formula with a concentration of Tween 80 and Span 80 of 10 grams and 3 grams, respectively. The particles are a spherical smooth shape and demonstrate an efficacy of 94.117% in inhibiting tyrosinase activity.